From Transactions to Trust: How Service Quality Drives Customer Satisfaction in Digital Banking - Mahato, Surendra; Kharel, Shreekrishna (The Mega Journal, 2025)
This article seeks to examine the impact of quality of digital banking services on customer satisfaction using quantitative research design with a mix of descriptive and analytical approaches. A sample of 384 customers who used digital banking were selected and observed via a survey using Structured Queries, the study measured seven dimensions of efficiency, system availability, fulfillment, privacy, contact responsiveness and Website design. Results from the multiple linear regression analysis also indicated that all dimensions do have positive and significant effect on customer satisfaction. The strongest predictor was site design were the strongest associated features as was contact. The availability of the system and its responsiveness. Other things also sustained him: privacy, fulfillment and efficiency for starters. Findings Confirmatory analysis of the E-S-QUAL model and the importance of secure, user-centered, reliable digital encounters that enhance satisfaction, specifically in emerging markets.